THE AUTHORITY OF BANK INDONESIA AS A STATE INSTITUTION IN THE DISTRIBUTION OF CORPORATE SOCIAL RESPONSIBILITY (CSR) - Sari, Lilik Rosita; Endarto, Budi (LPPM STIH Putri Maharaja, 2025)
Corporate Social Responsibility (CSR) or Social and Environmental Responsibility (TJSL) constitutes a legal obligation imposed on companies as part of their responsibility toward society and the environment. Normatively, CSR regulation in Indonesia is directed toward limited liability companies, particularly those operating in sectors related to natural resource utilization. However, recent developments have raised legal questions about the implementation of CSR-like programs by Bank Indonesia, an independent state institution. This study employs normative legal research using statute, conceptual, and case approaches. The findings demonstrate that CSR or TJSL obligations are explicitly regulated under Law No. 40 of 2007 concerning Limited Liability Companies, Government Regulation No. 47 of 2012, and the Minister of State-Owned Enterprises Regulation No. PER-05/MBU/04/2021. Conversely, Bank Indonesia is governed by Law No. 23 of 1999 as amended by Law No. 6 of 2009 and is not a corporate entity subject to CSR obligations. From an administrative law perspective, the absence of explicit attribution of authority indicates that the implementation of CSR by Bank Indonesia exceeds its statutory mandate. This study highlights the normative boundaries of administrative discretion and contributes to legal discourse by examining CSR practices within non-corporate state institutions.